Factors Affecting Cyberbullying Involvement Among Students of Northwestern University - Mark Angel P. Bagasol; Virgilio T. Balalio Jr.; Romie Dane D. Balanay; Jonathan Balantac; Mark April P. Barbado; Kween Charlette B. Velasco; Jonah B. Badua (Research Synergy Foundation, 2022)
Cyberbullying has emerged as a timely and relevant issue. Almost all students are active in using gadgets and exposed to social media platforms, making them vulnerable to cyberbullying. This study determined the factors associated with cyberbullying involvement of students of Northwestern University. It specifically answered the demographic profile of students, perceived factors influencing students' involvement in cyberbullying, its effects, and their coping mechanisms as the basis of coming up with Information-Education-Communication material. A quantitative-descriptive method was used using IPO. A survey questionnaire was used and distributed online using Google forms. There were 351 participants from different colleges. Frequency, percentage, and weighted mean are used to analyze the data. Findings revealed that Medium and school are the most significant factors influencing students' involvement in cyberbullying. The perceived effects of cyberbullying provide a risk to mental and physical health, lack of confidentiality or privacy, and connection to real life. It also generates mood, sleep, eating habits, or low self-esteem. Being with peers, understanding one's behavior, and focusing on studies are dominant coping mechanisms. Since this study is limited only to college students in private institutions, it offers future researchers to investigate the perception of students in public institutions. Further, researchers may also study parents' perceptions of cyberbullying since they play a vital role in protecting their children in this critical issue. This study on cyberbullying was conducted during the pandemic when students were exposed to technology and social media involving college students in a private institution.